Economics of art and culture invited papers at the 12th international conference of the Association of Cultural Economics International - Ginsburgh, Victor (Contributions to economic analysis ;, 2003)
This volume contains a large selection of the invited papers given at the Twelfth Conference of the Association of Cultural Economics International held in Rotterdam in 2002. Two sessions were devoted to what came to be called the cultural industries (movies, television, media, etc.). Two dealt with the history of art and music markets. The last two were more policy oriented. One was devoted to the management of built heritage which becomes larger every year, and will be in need of more and more public funding. The invited speakers in the last session had spent, or are still spending, some or most of their time in the real world, and try to discuss how cultural economists can contribute to alleviate the hard life of those who have to manage culture.Choices necessarily meant that many fields in which active research is alive were not dealt with, in particular, the contemporary functioning of art markets, artists' labor markets, museums and their management, aesthetic choices and tastes, the meaning of quality in the arts, etc. In this volume, the papers given in the six sessions are reshuffled and grouped into three parts: the cultural industries, historical aspects, and policy issues including the management heritage.